Preparation and evaluation of controlled release tablets of carvedilol - Setti, M L Varahala; Ratna, J Vijaya (Asian Journal of Pharmaceutics (AJP), 2014)
The objective of the present investigation is to design and evaluate controlled release tablets of carvedilol, employing synthetic polymers like polyethylene oxides, of different molecular weights as release retarding materials and to select the optimized formulation based on the pharmacokinetics of carvedilol. Matrix tablets each containing 80 mg of carvedilol were formulated employing PEO N60 K, PEO 301, and PEO 303 as release-retarding polymers and Î² Cyclodextrin and HP Î² cyclodextrin as release modulators from the matrix. Carvedilol release from the formulated tablets was very slow. Hence the release was modulated with the use of cyclodextrins. The dissolution from the matrix tablets was spread over more than 24 hours and depended on the type of polymer, its concentration and the type of cyclodextrin used. All the matrix tablets prepared using polyethylene oxides showed very good controlled release over more than 24 hours.The matrix tablets prepared using HP Î² cyclodextrin showed a higher dissolution rate and gave a dissolution profile that was comparable to the theoretical sustained release needed for once-a-day administration of carvedilol. The drug release mechanism from the matrix tablets was found to be quasi Fickian mechanism.